1992
DOI: 10.1111/j.1399-0004.1992.tb03652.x
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype/phenotype correlation in females with short stature

Abstract: Temtamy SA, Ghali I, Salam MA, Hussein FH, Ezz EHAA, Salah N. Karyotype/phenotype correlation in females with short stature. Clin Genet 1992:41: 147–151. We studied 60 females who presented with short stature. The main aim was to determine the effect of karyotype variation on phenotype. A somatic feature score was calculated for each case depending on the presence of 17 clinical somatic changes known to occur in Turner syndrome. Karyotype studies showed the following results: 45, X (n = 22): 46, XX (n= 11); 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
4
9
0
2
Order By: Relevance
“…It is possible that the etiology of recurrent OM is multifactorial, and perhaps it is related to lymphatic hypoplasia or the aberrant anatomic shaping of the structures derived from the first and second brachial arches. 10,24 The incidence of CHL among our patients was 10.7%, which is within the range (6%e44%) reported by others (Table 1). 4,7 These studies have found that tympanic membrane pathology and chronic middle ear disease, from middle ear effusion and repeated OM in the childhood, were the principal causes for CHL in TS.…”
Section: Discussionsupporting
confidence: 74%
“…It is possible that the etiology of recurrent OM is multifactorial, and perhaps it is related to lymphatic hypoplasia or the aberrant anatomic shaping of the structures derived from the first and second brachial arches. 10,24 The incidence of CHL among our patients was 10.7%, which is within the range (6%e44%) reported by others (Table 1). 4,7 These studies have found that tympanic membrane pathology and chronic middle ear disease, from middle ear effusion and repeated OM in the childhood, were the principal causes for CHL in TS.…”
Section: Discussionsupporting
confidence: 74%
“…Firstly, early defects in lymphatic channels (lymphatic hypoplasia) cause persistent lymphatic effusions in the middle ear cleft, predisposing to adhesions, impairing aeration and drainage. Secondly, aberrant anatomic shaping of structures derived from the first and second brachial arches leads to brachycephaly and high-arched palate in high numbers of TS patients [8,9], causing abnormally horizontal Eustachian tubes, and possible palatal dysfunction predisposing to otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…A estatura nos casos de ST foi significativamente mais baixa que no grupo sem ST, como também foi observado por outros autores 12 . Entre as pacientes com ST, praticamente 50% tinham escore z da estatura abaixo de -3,00, contra 31% daquelas sem ST. Além disso, cerca de 25% das pacientes com ST tinham escore z abaixo de -4,00 contra apenas 11% daquelas sem ST. Assim sendo, quanto maior o deficit em estatura, maior a probabilidade de que a paciente seja, de fato, portadora da ST.…”
Section: Discussionunclassified
“…A estatura em escore z das portadoras de ST no momento do diagnóstico (-3,09±1,34) foi semelhante à observada por outros autores (-3,51±1,7) 12 . Chama a atenção, porém, que quase 50% dos casos diagnosticados após os 18 anos tinham estatura dentro da normalidade, corroborando a observação, na prática clínica, de que o menor comprometimento em estatura tende a determinar diagnóstico mais tardio, possivelmente por dificultar a suspeita precoce por pediatras.…”
Section: Discussionunclassified